Penanaman Tanaman Obat Di Desa Amongrogo Kecamatan Limpung Kabupaten Batang - Nugroho Ariya Putra; Andarina Aji Pamurti (Universitas Semarang, 2023)
The potential for agriculture and plantations in Amongrogo Village, Limpung District, Batang Regency is enormous. This is because the majority of the people of Amongrogo Village work as farmers and agricultural land in the village is categorized as productive land. Based on the existing conditions, the community needs education about the importance of growing medicinal plants for daily life. The function of medicinal plants can meet the needs of traditional medicine for the community. The activity of planting medicinal plants is by utilizing vacant land as a place for planting. The benefit of this activity is to increase public knowledge about the importance of medicinal plants. Planting of medicinal plants is done using polybag media. The selection of this medium is based on planting through polybags does not require a large area of land and is quite affordable. From the community service activities that have been carried out, the community can see how to grow medicinal plants and understand the importance of medicinal plants for everyday life and can apply them in their respective environments.